Prognostic value of adipokines in patients with myocardial infarction and glucose metabolism disorders - Kamila Kahramonzhonovna Kholmatova; Irina Vladimirovna Dvoryashina; Irina Adolfovna Fomkina; Tatiana Vyacheslavovna Supryadkina (Сахарный диабет)
Aims. To evaluate the prognostic value of adipokines in patients with myocardial infarction (MI) and various glucose metabolism disorders. Materials and Methods. Consecutive patients aged ?80 years and diagnosed with MI (380 patients, 63.4% males) were examined. The patients were classified into four groups: I, with normal glucose tolerance; II, with prediabetes; III and IV - with newly detected and previously diagnosed type 2 diabetes mellitus, respectively. Levels of insulin, C-peptide and cortisol during glucose tolerance test and basal levels of apolipoproteins AI, B100, leptin and adiponectin were determined in 113 patients with Q MI. Cardiovascular events were analysed for the next 2 years after MI. Logistic regression analysis was used to identify the risk factors of poor prognosis after MI. Results. Elevated levels of leptin with decreased levels of adiponectin were observed in all MI patients independent of the degree of glucose metabolism disturbance. A linear trend of leptin level increase was observed starting from group I to group IV (Jonckheere?s test: J=2218.0; z=3.411; р=0.001). Multiple regression analysis showed that the basal insulin level was an independent predictor of death during the 2 years after MI (OR=0.639; р=0.033). MI prior to hospitalisation (OR=5.633; р=0.013), basal hypercortisolaemia (OR=5.435; р=0.016), glycaemia (OR=1.213; р=0.023) and heart rate (OR=1.051; р=0.032) on admission were associated with the occurrence of repeated MI. Leptin levels (OR=1.018; р=0.031) and creatine kinase-MB fraction (OR=1.009; р=0.018) were risk factors of the occurrence of the combined end-point of cardiovascular events. Conclusion. An imbalance of adipokines was observed in MI patients regardless of the presence of glucose disorders. The levels of leptin, glycaemia, insulin and basal hypercortisolaemia were significantly associated with the occurrence of cardiovascular events during the late post-infarction period.